Brainstorm : the power and purpose of the teenage brain - Siegel, Daniel J., 1957- (New York : Jeremy P. Tarcher/Penguin, a member of Penguin Group (USA), 2013)
Discusses a number of ways that the teenage brain processes information.
Publisher's Weekly, October 2013
Kirkus Review, November 2013
Includes index.
Adult
Adult.
Publisher's Weekly
Keywords: Adolescent psychology; Brain; Cognition in adolescence; Adolescent psychology; Brain; Theory of knowledge